Occurrence, properties and suitability of sandy beach ridges (BRIS) soils in the Kelantan-Terengganu plains, Peninsular Malaysia - Ismail, Roslan (2012)
A study was conducted to understand the occurrence, properties and productivity of the sandy beach ridges (BRIS) soils in the Kelantan-Terengganu Plains, Peninsular Malaysia. It consist of Baging, Rusila, Rhu Tapai (profile P1), Rudua (profile P2) and Jambu Series (profile P3). Three of the latter soil series have spodic horizon at different depth, hence classified as Spodosols. The landscapes were marked with Casuarina sumatrana and Zoysia matrala that produce acid humus, mean annual temperature of 32oC, and high rainfall (up to 3500 mm/year) with 3 ridges (at most ±5 m.a.s.l) and swales formed by the eustatic sea effect. The ridges area stated in the order of: 1) the youngest ridge, 2) the intermediate ridge, and 3) the innermost ridge. Entisols (Baging Series) found in ridge 1, while in ridge 2 (profile P1 and P2), spodic horizon samples dates 3000 year-old, and 6000 yearold in ridge 3 (profile P3). Rusila Series is often flooded, thus classification is difficult. Soil samples were collected in two different methods, i)soil samples collected based on depth of 0-15, 15-30, 30-45 and 45-60 cm were used to study the soil suitability for crop production and ii) three Spodosols soils pits (profile P1, P2 and P3) were described based on genetic horizon their organic acids were studied to clarify the formation of spodic horizon. All of the samples were subjected to pyhsico-chemical analyses. BRIS soils are sandy (>95% sand) mainly single grain, high net leaching (>12 cm/hour), pH (4-5), Corg (0.2-2.0%), CEC <5 cmolc/kg, low EC, high bulk density (1.65 g/cm3) and low water content (<10 vol.%). Mineralogical study showed quartz dominance with traces of feldspar, mica, gibbsite, hematite, halloysite and anatase that indicate intense weathering and/or leaching have taken place in the plains. Organic acids functional group (by FTIR spectroscopy) and their content (by humic acid analyses) were determined, and the data showed dominance of sharp and strong C-O group complexes and –COOH group (2000 – 3000 cm-1) of carboxylic groups that known to corrode quartz, thus soil losses Si and may gain Fe and/or Al in the soil profiles, with 13C NMR spectra further confirms the findings. Oxalic acid (6 μM) and citric acid (12 μM) were dominant with traces of other LMW organic acids in the spodic horizon. These acids has strong affinity to form metal complexes with Fe and/or Al. Carboxylic acid groups occurs naturally in plant and animals; hence this corresponds to the presence and decomposition of Recent and Sub-recent marine deposits in the BRIS landscape. In thousands of years, carboxylic acids form organometal-chelates with Fe and/or Al metals, and transport the sesquioxides to subsoil-B horizon, accumulate and undergo periodic desiccation and precipitation,giving rise to spodic horizon.